팬번역 공동체에서의 학습과 지식 창출: ‘실천공동체’ 개념을 중심으로 - 강지혜; 유한내 (번역학연구, 2023)
This study examines the concept of ‘communities of practice’ and its practical implications in the realm of translation studies, with a specific focus on research into community-oriented amateur translation. Drawing on Wenger’s 1998 conception of communities of practice, this study analyzes how learning and knowledge generation unfold within a fan translation community known as BTS TRANS by employing a qualitative research method, specifically a Focus Group Interview (FGI). The analysis underscores that BTS TRANS embodies a distinct community identity that is dedicated to meticulously translating video content related to BTS. This identity effectively shapes and governs the entire spectrum of their activities. As this identity-driven interaction thrives within the community, members organically and flexibly acquire translation skills, culminating in the creation of translation-related knowledge. Illustrated through the case study of BTS TRANS, the communities of practice framework emerges as a valuable analytical tool. It vividly illustrates how the dynamics of interaction and communication among community members facilitate learning, skill enhancement, and the organic generation of knowledge.
Keywords: communities of practice; situated learning; identity; knowledge creation; interaction; fan translation community; 실천공동체; 상황 학습; 정체성; 지식 창출; 상호작용; 팬번역 공동체